Elucidating the role of pigment epithelium-derived factor (PEDF) in metabolic PCOS models. Issue 2 (February 2020) - Silber, Michal; Miller, Irit; Bar-Joseph, Hadas; Ben-Ami, Ido; Shalgi, Ruth
Abstract : PCOS is the most common endocrinopathy in women; associated with obesity and insulin resistance (IR). IR leads to accumulation of advanced-glycation-end-products (AGEs) and their receptor, RAGE. PCOS patients have increased levels of vascular endothelial growth factor (VEGF), interleukin 6/8 (IL-6/8) and anti-Mϋllerian-hormone (AMH). PEDF is a secreted-glycoprotein known for its anti-angiogenic and anti-inflammatory properties. We aimed to elucidate the role of PEDF in the pathogenesis and treatment of PCOS. We used a prenatal PCOS mouse model and fed the female offspring a high-fat diet, inducing metabolic PCOS (met.PCOS) characteristics. Female offspring were divided into three groups: control; met.PCOS; met.PCOS + recombinant PEDF (rPEDF). Met.PCOS mice gained more weight, had elevated serum IL-6 and higher mRNA levels of AMH, PEDF and RAGE in their granulosa cells (GCs) than met.PCOS + rPEDF mice. An in vitro Met.PCOS model in human GCs (KGN) line was induced by prolonged incubation with insulin/AGEs, causing development of IR. Under the same conditions, we observed an elevation of VEGF, IL-6/8 mRNAs, concomitantly with an increase in PEDF mRNA, intracellular protein levels, and an elevation of PEDF receptors (PEDF-Rs) mRNA and protein. Simultaneously, a reduction in the secretion of PEDF from GCs, was measured in the medium. The addition of rPEDF (5 nM) activated P38 signaling, implying that PEDF-Rs maintained functionality, and negated AGE-induced elevation of IL-6/8 and VEGF mRNAs. Decreased PEDF secretion may be a major contributor to hyperangiogenesis and chronic inflammation, which lie at the core of PCOS pathogenesis. rPEDF treatment may restore physiological angiogenesis inflammatory balance, thus suggesting a potential therapeutic role in PCOS.